Ответы и объяснения

2012-05-26T09:38:39+00:00

×⁴+1                            ×⁴ + 2ײ + 1 - 2ײ                  (ײ +  1)²  - 2ײ            

________         =         _________________        =__________________  =

ײ+×√2+1                       ײ + ×√2 + 1                        ײ + ×√2 + 1              

 

           (ײ +  1)²  - ( √2×)²          (х²+  1 + √2х )(ײ +  1 - √2× )

=      ____________________= ______________________________ =   ײ - √2× +  1

           ײ + ×√2 + 1                                     х²+ х√2 + 1